Modelling and simulation of two axes gimbal fuzzy PI stabilization system in the presence of feedback sensors noise. Issue 1 (August 2021) - Fathi, A; Kamel, A M; Elfarouk, A O; Elhalwagy, Y
Abstract: The missile guidance in terminal phase is an optimization problem as the miss distance should be minimized. The optimization of missile miss distance is highly affected by the missile seeker performance. Design of gimbal control system suffers always from feedback sensors noise which leads to system instability. In this paper, a promising design of the fuzzy PID controller for a missile seeker gimbal is proposed considering the feedback sensor noise with practical gyro transfer function calculated based on real experimental measurements utilizing MATLB system identification toolbox. Also, the mathematical model of two stabilized axes gimbal. Stabilization is achieved considering the missile motion parameters such as rates, torques and coupling between yaw and roll channels. A Matlab simulation is carried out for evaluating the proposed system modelling and to test the robustness of the fuzzy PID controller in the presence of feedback sensor noise. A comparative analysis with PI based controller is conducted to evaluate the performance of the proposed controller which presents sufficient enhancement to the missile gimbal stability parameters.